An Analysis of Factors Affecting Brand Loyalty to E-Commerce Users Mediated by Brand Trust - Kartika Wulandari Siamanjuntak; Fendy Cuandra (Kawanua International Journal of Multicultural Studies, 2023)
This study aimed to analyze the factors that influence brand loyalty, and the role of brand trust as an intervening variable in E-Commerce users. Two hundred and fifty (250) respondents participated in the sample data collection. The results of this study found that brand trust and brand image did not affect brand trust. Brand positioning, customer satisfaction, and brand awareness had a significant effect on brand trust. And, brand trust had a significant effect on brand loyalty.